The quasi-static cyclic behaviour of CFRP-to-concrete bonded joints: An experimental study and a damage plasticity model. (15th December 2017) - Zhou, Hao; Fernando, Dilum; Chen, Guangming; Kitipornchai, Sritawat
Highlights: FRP-to-concrete bonded joints were tested under quasi-static cyclic loading. Bond-slip curves of FRP-to-concrete bonded joints were obtained. A damage plasticity model regarding quasi-static cyclic behaviour is proposed. The proposed model shows better agreement with test results among existing models. Abstract: In reinforced concrete structures strengthened using externally bonded fibre reinforced polymer (FRP) laminates, the performance of the bonded interface is vital to the performance of the strengthened structure. Extensive research has been carried out to study the behaviour of FRP-to-concrete bonded interfaces under quasi-static monotonic loading. However, only limited work has been done on understanding the behaviour of such bonded joints under quasi-static cyclic loading, which is a key issue to be addressed in modelling the long-term performance of carbon FRP (CFRP)-to-concrete bonded joints. This paper presents an experimental and theoretical study aimed at investigating and modelling the behaviour of CFRP-to-concrete bonded joints under quasi-static cyclic loading. A series of CFRP-to-concrete single lap shear pull-off tests were carried out under both quasi-static monotonic and cyclic loading. A thermodynamically consistent damage plasticity model where the damage parameter is defined as a function of the ratio between dissipated and total interfacial fracture energy was then proposed for modelling the constitutive behaviour of the CFRP-to-concrete bonded interface under quasi-static cyclic loading. The function to define the damage parameter was calibrated using the test results. Proposed model was then used to predict the bond-slip and load–displacement behaviour of the single lap shear pull-off tests. Results were compared with the experimental results and the prediction from two of the other existing models. Compared to the existing numerical models, the proposed model showed a better agreement with the test results.